PERAN MEDIA SOSIAL DALAM MEMBANGUN DAN MENAMPILKAN CITRA DIRI KEISLAMAN DIKALANGAN MADRASAH - Eka pratiwi, Aisyati; Ayu Kumala, Firda; Sarmita; Khairul Anam, Rifqi (As-Sulthan Journal of Education, 2025)
The use of social media among students of madrasah has become increasingly prevalent and plays a significant role in shaping their religious identity. This study aims to explore how madrasah students use social media to build and present their Islamic self-image, as well as how social recognition from peers influences this process. The method used is library research with a qualitative approach, analyzing relevant literature on social media, adolescent identity, and Islam. The main findings indicate that social media serves as a platform for madrasah students to express their religious identity through various forms of content such as religious preaching, calls to worship, and sharing religious knowledge. Social recognition from peers plays a key role in strengthening their Islamic self-image, although there is pressure to present an idealized and performative image. In conclusion, social media has transformed into an important space for the formation of religious identity among madrasah students, but it also brings psychological and social impacts that need to be considered